2018
DOI: 10.1016/j.jenvman.2017.10.063
|View full text |Cite
|
Sign up to set email alerts
|

Tracing the role of endogenous carbon in denitrification using wine industry by-product as an external electron donor: Coupling isotopic tools with mathematical modeling

Abstract: Nitrate removal through enhanced biological denitrification (EBD), consisting of the inoculation of an external electron donor, is a feasible solution for the recovery of groundwater quality. In this context, liquid waste from wine industries (wine industry by-products, WIB) may be feasible for use as a reactant to enhance heterotrophic denitrification. To address the feasibility of WIB as electron donor to promote denitrification, as well as to evaluate the role of biomass as a secondary organic C source, a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 51 publications
2
12
0
Order By: Relevance
“…However, to promote groundwater remediation within the aquifer, liquid compounds are preferable as they could be easily applied by injection through already constructed wells. In this context, a wine industry residue was recently tested to promote heterotrophic denitrification (Carrey et al, 2018). The use of whey may also be an economically feasible solution to attenuate NO3pollution, while providing waste recycling.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, to promote groundwater remediation within the aquifer, liquid compounds are preferable as they could be easily applied by injection through already constructed wells. In this context, a wine industry residue was recently tested to promote heterotrophic denitrification (Carrey et al, 2018). The use of whey may also be an economically feasible solution to attenuate NO3pollution, while providing waste recycling.…”
Section: Introductionmentioning
confidence: 99%
“…The observed isotopic fractionation (ε) of N and O from dissolved NO3can be used to estimate the efficacy of induced denitrification (Mariotti et al, 1988). Furthermore, the isotopic characterization (δ 13 C) of dissolved organic and inorganic carbon (DOC and DIC) during denitrification might provide knowledge on the fate of the added organic C source (Carrey et al, 2018;Nascimento and Krishnamurthy, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Since the use of pure reagents such as glucose, acetate, or ethanol may be expensive in long-term treatments, the use of industrial or agricultural residues that are rich in organic C could represent a more sustainable solution. Solid products such as animal or vegetal waste (Grau-Martínez et al, 2017;Si et al, 2018;Trois et al, 2010), as well as industrial liquid by-products (Carrey et al, 2018;Margalef-Marti et al, 2019), have already been reported as being useful for promoting denitrification.…”
Section: Introductionmentioning
confidence: 99%
“…The C/N ratio is the ratio of COD to total nitrogen (TN) or biochemical oxygen demand (BOD) to TN [8,9]. It is not only a key factor for microorganism growth, but it is also an important wastewater quality index [10][11][12].…”
Section: Introductionmentioning
confidence: 99%
“…The optimal C/N ratio for conventional aerobic treatment is 20. In recent years, low C/N ratios (<5) have been frequently studied [9][10][11] and so low C/N ratios of 5, 2, 1, 0.5 and 0.1 were also included. A middle value of 10 was also chosen between 20 and 5.…”
Section: Introductionmentioning
confidence: 99%